The Mediating Effect of Self-Efficacy on Perceived Supervisor Support on Self-Perceived Employability in Generation Z Participating in the Certified Internship and Independent Study Program - Lintang, Brigitta Elizabeth; Nindyati, Ayu Dwi; Wicaksana, Seta A (Universitas Negeri Malang, 2024)
According to demographic trends, Generation Z was 25 percent of the labor force by 2030. Generation Z needs extra preparation because of a lack of work experience and has a propensity for having negative attitudes at work. Participating in an internship program like the Certified Internship and Independent Study is one of those preparations. Participants in this internship gain both practical work and supervised experience by their supervisor. This research aimed to investigate if the existence of self-efficacy can influence self-perceived employability as a mediator and perceived supervisor support as a predictor. The research method used a quantitative approach to 160 Generation Z members participating in the batch 3 internship program (25.5 percent of the population) at an IT company. Hypothesis testing was carried out with the mediation analysis model in the medmod module in Jamovi 2.3.26. The main result was that self-efficacy could partially mediate the effect of perceived supervisor support on self-perceived employability. This means that the existence of self-efficacy can indirectly increase the influence of perceived supervisor support on self-perceived employability. The direct influence of perceived supervisor support on self-perceived employability is smaller than when involving self-efficacy as a mediator. Based on this result, interventions can be made to strengthen the self-efficacy of internship participants, for example, by providing a strong experience so that the supervision program during an internship can strengthen the self-perceived employability of internship participants. In the end, the intern participants can feel the added value of their internship program.